2019
DOI: 10.1139/cgj-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

A strength criterion for frozen clay considering the influence of stress Lode angle

Abstract: To investigate the influence of stress Lode angle on frozen soil, a series of directional shear tests was conducted on artificial frozen clay at three temperatures (–6, –10, and –15 °C) and five stress Lode angles (θσ = –30°, –16.1°, 0°, 16.1°, and 30°) using a hollow cylindrical apparatus. An elliptical function was proposed according to the strength envelope evaluation with the mean principal stress (p) in the p–q plane. In addition, generalized nonlinear strength theory (GNST) was introduced in the π plane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Compared with true triaxial compression apparatus, the principal stress level and its orientation under complex stress paths can be achieved comprehensively by controlling the axial load, torque, and inner and outer cell pressures independently using a torsional shear apparatus to replicate C-T action. Early torsional shear apparatuses were mainly used in the study of soft soils [27], but were later extended to frozen soils [28] and rocks [29,30], with the aim of developing strength criteria under complex stress states. But the aforementioned methods do not allow the visualization of specimens, which has limited our understanding of the microcosmic mechanisms therein.…”
Section: Geofluidsmentioning
confidence: 99%
“…Compared with true triaxial compression apparatus, the principal stress level and its orientation under complex stress paths can be achieved comprehensively by controlling the axial load, torque, and inner and outer cell pressures independently using a torsional shear apparatus to replicate C-T action. Early torsional shear apparatuses were mainly used in the study of soft soils [27], but were later extended to frozen soils [28] and rocks [29,30], with the aim of developing strength criteria under complex stress states. But the aforementioned methods do not allow the visualization of specimens, which has limited our understanding of the microcosmic mechanisms therein.…”
Section: Geofluidsmentioning
confidence: 99%
“…Various criteria have been developed to describe the strength characteristics of geomaterials, such as Lade-Duncan criterion, Drucker-Prager criterion, Mises criterion, and spatially mobilized plane strength criterion. According to a series of directional shear tests, Chen et al [28] found that generalized nonlinear strength theory (GNST) developed by Yao et al [42] can well present the strength evolution of frozen samples. The simulation data of GNST was in good agreement with test results in π plane.…”
Section: Shape Function In πmentioning
confidence: 99%
“…As for frozen soils, the strength characteristics can be rather complicated since the pore ice crystals can be crushed and melt at relatively high stresses. Many investigations were performed to research the strength of frozen geomaterials [21][22][23][24][25][26][27][28]. Compared with general geomaterials, the influence factor of frozen soil strength is more complicated, such as pressure, dry density, and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Many constitutive models (e.g., hyperelastic model, nonlinear elastic model, and viscoelastic-plastic model) have been established to describe the mechanical features of frozen soils [9][10][11][12][13][14]. In addition, on the basis of continuous damage theory, some constitutive models of frozen soil have also been established.…”
Section: Introductionmentioning
confidence: 99%